The Onset of Asymmetric Combustion of Aluminum Particles. Issue 2 (25th January 2022) - Trottini, E.; Higuera, F. J.
ABSTRACT: Combustion of an aluminum droplet in an oxidizer atmosphere is known to proceed in several stages. Ignition is followed by a first combustion stage in which the droplet is surrounded by a spherical diffusion flame, but this flame and the conditions at the droplet surface eventually cease to be uniform, giving way to a second combustion stage characterized by an asymmetric, spinning flame. This is followed by a final stage in which an oxide cap develops in the droplet. Oxygen reaches the surface of the burning droplet as aluminum suboxides and other oxygenated species produced at the flame, and dissolves in the liquid. The beginning of asymmetric combustion is associated with the appearance of an oxygen-rich liquid phase that is immiscible with aluminum. A simple model of the onset of asymmetric combustion is proposed that focuses on the adsorption of A l O at the surface, the heterogeneous reaction generating A l 2 O 3, and the transfer of this species to the liquid bulk. Other aspects of the combustion are drastically simplified. The model shows that spherically symmetric combustion becomes unstable at a certain time, after which oscillatory perturbations develop that resemble the spinning flame observed experimentally. The instability depends on the interplay of adsorption of A l O and production of A l 2 O 3 at the surface, and disappears when the second of these processes is very fast.